Pengembangan Inovasi Sekolah Orangtua dalam Menciptakan Segitiga Emas Lembaga Pendidikan Islam - Siti Auliyatus Sholawati (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2019)
This study discusses the form of parent schools that answer global problems in children's education at school. The purpose of this study was to determine the impact and evaluate of the innovation development program of parent schools in creating the golden triangle of institutions carried out in the Pondodk Pesantren At-Thoyyibah Sukodono Sidoarjo. Data collection has been done through observation, interviews and analysis of documents from several sources. Based on the results of data analysis, the results show that the innovation development program of the parent school refers to the quality accreditation that the institution has, the hope of being formed is to be able to connect the golden triangle chain, namely school, parents and students. The parent school activities that are carried out are recitation/memorization of the Qur'an using the Wafa method, discussion of child development, parenting material, outbound, social gathering, and hobbies. The supporting factors of this program are good management support, and supporting school resources, while the inhibiting factor is that there are still many very busy parents who have not been able to take part in parental school activities to the fullest. To overcome this, several efforts have been made, namely by applying parenting every one year twice.